Use of bacterial communities to assess the ecological health of a recently restored stream - G Lear; P‐Y Ancion; J Harding; GD Lewis (New Zealand Journal of Marine and Freshwater Research, 2012)
We assess the utility of bacterial community data for providing an indication of stream health in a recently ‘restored’ urban stream. A community DNA fingerprinting technique was used to characterise the bacterial community within Okeover Stream, and a lesser impacted, nearby stream. No significant differences in bacterial community structure were detected between streams. However, further investigation revealed highly elevated levels of Zn, Pb and Cu associated with microbial biofilms in Okeover Stream and an increased abundance of genes encoding for bacterial resistance to Co, Zn and Cd. Benthic invertebrates were also sampled, confirming that despite recent attempts at stream restoration, the ecological health of the Okeover Stream remains poor. While the analysis of macroinvertebrate communities appeared to provide a more informative measure of overall stream health, we show that the targeted analysis of bacterial functional genes can be used to identify possible causes of declining ecological health.